Gut fungi enhances immunosuppressive function of myeloid-derived suppressor cells by activating PKM2-dependent glycolysis to promote colorectal tumorigenesis - Zhiyong Zhang; Yaojun Zheng; Ying Chen; Yuxin Yin; Yuxi Chen; Qianyu Chen; Yayi Hou; Sunan Shen; Mingming Lv; Tingting Wang (Experimental Hematology & Oncology, 2022)
Abstract Background Accumulating evidence implicates that gut fungi are associated with the pathogenesis of colorectal cancer (CRC). Our previous study has revealed that Candida tropicalis (C. tropicalis) promotes colorectal tumorigenesis by enhancing immunosuppressive function of myeloid-derived suppressor cells (MDSCs) and increasing accumulation of MDSCs, but the underlying mechanisms remain unestablished. Methods Bone marrow–derived MDSCs were stimulated with C. tropicalis. RNA-sequencing analysis was performed to screen the differentially expressed genes. Quantitative real-time PCR and western blot were used to measure the expression of related proteins. Co-culture assay of MDSCs and CD8+ T cells was used to determine the immunosuppressive ability of MDSCs. Metabolomic analysis was conducted to detect metabolic reprogramming of MDSCs. Aerobic glycolysis of MDSCs was assessed by extracellular acidification rate (ECAR), glucose consumption and lactate production. A CAC mouse model was induced by AOM and DSS to determine the therapeutic action of TEPP-46. IHC and immunofluorescence were performed to examine the expression of PKM2, PKM2 (p-Y105) and iNOS in human CRC-infiltrated MDSCs. Results C. tropicalis facilitates immunosuppressive function of MDSCs by increasing the expression of iNOS, COX2 and NOX2, production of nitric oxide (NO) and reactive oxygen species (ROS). Mechanistically, C. tropicalis facilitates the immunosuppressive function of MDSCs through the C-type lectin receptors Dectin-3 and Syk. C. tropicalis-enhanced immunosuppressive function of MDSCs is further dependent on aerobic glycolysis. On the one hand, NO produced by MDSCs enhanced aerobic glycolysis in a positive feedback manner. On the other hand, C. tropicalis promotes p-Syk binding to PKM2, which results in PKM2 Tyr105 phosphorylation and PKM2 nuclear translocation in MDSCs. Nuclear PKM2 interacts with HIF-1α and subsequently upregulates the expression of HIF-1α target genes encoding glycolytic enzymes, GLUT1, HK2, PKM2, LDHA and PDK1, which are required for the C. tropicalis-induced aerobic glycolysis of MDSCs. Blockade of PKM2 nuclear translocation attenuates C. tropicalis-mediated colorectal tumorigenesis. The high expression of PKM2, PKM2 (p-Y105) and iNOS in CRC-infiltrated MDSCs correlates with the development of human CRC. Conclusion C. tropicalis enhances immunosuppressive function of MDSCs via Syk-PKM2-HIF-1α-glycolysis signaling axis, which drives CRC. Therefore, we identify the Syk-PKM2-HIF-1α-glycolysis signaling axis as a potential therapeutic target for CRC.